Optimum saving and growth: Harrod on dynamic welfare economics - Mauro Boianovsky (Duke University, Center for the History of Political Economy (CHOPE), 2017)
In the 1960s and 1970s Harrod shifted the emphasis of his research in economic dynamics from the study of business cycles (instability principle) to the investigation of the growth process. As part of that, he restated his concept of the natural growth rate as an optimum welfare rate. The present paper examines Harrod's dynamic welfare economics, built around his concept of optimum saving developed as a reaction to Ramsey's approach to capital accumulation. It is shown that, according to Harrod, the saving rate does not affect the long-run growth rate of per capita income, which is determined by technical progress. Moreover, the economy will grow at the natural (full employment) rate only if economic policy is able to bring saving to its "optimum" level in macroeconomic equilibrium. Harrod's interest in optimal growth was motivated by his double concern with growth policy in mature economies and economic development in poor countries.
Keywords: B22; O10; 330; Harrod; optimum saving; growth; dynamic welfare economics